2022
DOI: 10.1371/journal.pgph.0000137
|View full text |Cite
|
Sign up to set email alerts
|

Predict the incidence of Guillain Barré Syndrome and arbovirus infection in Mexico, 2014–2019

Abstract: The Dengue (DENV), Zika (ZIKV), and Chikungunya (CHIKV) virus infections have been linked to Guillain-Barré syndrome (GBS). GBS has an estimated lethality of 4% to 8%, even with effective treatment. Mexico is considered a hyperendemic country for DENV due to the circulation of four serotypes, and the ZIKV and CHIKV viruses have also been circulating in the country. The objective of this study was to predict the number of GBS cases in relation to the cumulative incidence of ZIKV / DENV / CHIKV in Mexico from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In addition, contacts could have presented paucisymptomatic and/or moderate forms of infection with the presence of IgM antibodies, while others would have been cured as IgG antibodies were detected. Hughes RAC et al supported this hypothesis by showing in 2005 that in most cases, it is difficult to isolate and identify the agent responsible for non-polio paralysis, as the diagnosis is usually made at an advanced stage of infection or after infection and often only serological tests are positive [ 19 , 20 ]. We looked for and documented an etiology other than poliovirus in the context of recurrent paralysis cases in DRC with a lack of technical facilities, but the late investigations could justify the non-detection of viral ribonucleic acid (RNA).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, contacts could have presented paucisymptomatic and/or moderate forms of infection with the presence of IgM antibodies, while others would have been cured as IgG antibodies were detected. Hughes RAC et al supported this hypothesis by showing in 2005 that in most cases, it is difficult to isolate and identify the agent responsible for non-polio paralysis, as the diagnosis is usually made at an advanced stage of infection or after infection and often only serological tests are positive [ 19 , 20 ]. We looked for and documented an etiology other than poliovirus in the context of recurrent paralysis cases in DRC with a lack of technical facilities, but the late investigations could justify the non-detection of viral ribonucleic acid (RNA).…”
Section: Discussionmentioning
confidence: 99%
“…[10] In Mexico, Chikungunya was introduced in 2014, followed by Zika in 2015, [5] along with epidemics of these viruses and Guillain-Barré syndrome from 2014 to 2017. [11,12] In 2019, during a dengue epidemic in Mexico caused by DNV-2, the most affected age groups were 10-14 and 15-19 years old. [13] This serotype co-circulated predominantly with DNV-1 between 2011 and 2013 and had low circulation in 2016 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Arboviral infections caused due to Dengue and Chikungunya virus were found in 4% of these cases [ 41 ]. Another study conducted in Mexico to predict the incidence of GBS owing to arboviral infections reported antecedent Zika and Dengue infections in GBS but intriguingly, GBS was not associated with antecedent Chikungunya infection [ 42 ]. Among studies conducted in India, one done in the northern region reported 11.5% (3/26) antecedent Dengue infection in GBS [ 43 ].…”
Section: Literature Review: Antecedent Infections In Gbsmentioning
confidence: 99%